HUBUNGAN ANTARA KONSEP DIRI DENGAN DISIPLIN SISWA - Lina Novita; Tustiyana Windiyani; Dina Aprilia Suhrawardi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
This research is with the design and model of Quantitative Research of Correlational Studies. The purpose of this study is to describe the relationship between self-concept and students discipline of students in V grade students of Kota Batu 02 State Elementary School Ciomas District Bogor Regency. The subject of this research is 80 students of class V Kota Batu 02 State Elementary School Ciomas District Bogor Regency. This research was conducted on the odd semester of Lesson 2018/2019. The results showed that the average of self-concept variable is 89,88, while the students discipline variable has an average of 90,95 thus the relationship of self-concept with students discipline in statistical analysis is indicated by the result of significance test and regression with regression equation ? =48,374 + 0,4737x. This means that each increase of one students discipline variable value is 0,4737 units. The strength of the relationship between self-concept and students discipline is shown by the correlation coefficient with r value of 0,48 which means have a relationship. The magnitude of the contribution of self-concept with students discipline is shown by the coefficient (r) of 0,23 with the coefficient of determination of 23%. This means that the increase or decrease in students discipline has a relationship by self-concept by 23%. Based on the results of the above research can be concluded that the relationship between self-concept and discipline of students in class V Kota Batu 02 State Element 02 Bogor Regency have a relationship.